Ammonia Vola Tilization as Influenced by Amendments in a Light Textured Alkali Soil - Sharma, B M; Aggarwal, R K; Kumar, Praveen (Annals of Arid Zone, 2016)
An alkali soil, treated with gypsum (50 and 100 per cent of its gypsum requirement) and flyash (8 and 15 per cent by weight of soil) and followed by leaching with water was studied for ammonia release and changes in available nutrient content There was drastic reduction in NH3 losses with the application of gypsum and flyash which was partly due to reduction in soil pH. The magnitude of reduction was higher in gypsum than flyash amended soil and increased with the dose of amendments. The treated soil showed significant increase in the availability of macro and micro nutrionts.